A Decrease in Bruch's Membrane Opening-Minimum Rim Area Precedes Decreased Retinal Nerve Fiber Layer Thickness and Visual Field Loss in Glaucoma. Issue 12 (December 2021) - Choi, Hyun Sup; Joo, Chan Woong; Park, Sung Pyo; Na, Kyeong Ik
Abstract : Précis: A decrease in Bruch's membrane opening-minimum rim area, which represents the optic nerve head (ONH), preceded a decrease in the peripapillary retinal nerve fiber layer thickness (RNFLT) and the visual field index (VFI). Purpose: This study aimed to investigate the relative comparison between a decrease in BMO-MRA, the peripapillary RNFLT, and the VFI, according to the severity of glaucoma. Materials and Methods: This retrospective cross-sectional study included 121 eyes (73 with open-angle glaucoma and 48 normal eyes). The ONH and retinal nerve fiber layer were analyzed using spectral domain optical coherence tomography, and VFI was obtained using the Humphrey Field Analyzer. The tipping points of RNFLT for VFI and BMO-MRA were estimated using broken-stick regression models. Polynomial regression analysis was performed, and the changes in the 3 parameters were expressed as a graph. Results: The tipping point of the RNFLT for the VFI was 88.62 μm [95% confidence interval (CI): 79.59-97.65; P =0.001]. The tipping point of the RNFLT for BMO-MRA was 60.00 μm (95% CI: 48.28-71.72; P =0.220). Above the tipping point, BMO-MRA decreased with a decrease in the RNFLT (slope=0.0135; 95% CI: 0.0115-0.0155; P <0.001); below the tipping point, BMO-MRA did not decrease significantly (slope=0.0002; 95% CI: −0.0177 to 0.0181; P =0.983). P olynomial regression analysis showed that with the progression of glaucoma, BMO-MRA decreased more rapidly, and this preceded a decrease in the RNFLT followed by a decrease in the VFI. Conclusion: The ONH parameter, BMO-MRA, showed a faster decrease than RNFLT and VFI in early glaucoma. BMO-MRA may help detect early glaucomatous damage and its progression.